The economic uses of Oral History: economic uses of Oral History - Gómez Martín, María; Cañal Fernández, Verónica (Clio. History and History Teaching, 2020)
The aim of this paper is to develop an interactive and motivating didactic proposal that encourages the involvement of universities students in subjects related to economic history. Through a methodology appropriate to oral history, the aim is to establish a link between students, historiographic research techniques and the historical evolution of their region in economic and social matters. The results of this project confirm that its application makes the learning process more meaningful, connects its participants to the world around them and helps them understand how history is made and written.